2021
DOI: 10.1182/bloodadvances.2021004824
|View full text |Cite
|
Sign up to set email alerts
|

Do age, fitness, and concomitant medications influence management and outcomes of patients with CLL treated with ibrutinib?

Abstract: Functional reserve of organs and systems is known to be relevant in predicting immunochemotherapy tolerance. Age and comorbidities, assessed by the cumulative illness rating scale (CIRS), have been used to address chemotherapy intensity. In ibrutinib era it is still unclear whether age, CIRS and ECOG-PS retain their predictive role on treatment vulnerability. In this 712 CLL patients series treated with ibrutinib outside clinical trials, baseline ECOG-PS and neutropenia, resulted as the most accurate predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 45 publications
(52 reference statements)
3
21
3
Order By: Relevance
“…Response rates appear instead rather similar across studies (Table 5). Likewise, discrepancies observed between patients treated in second or later line in our study and in clinical trials may be in part explained by the fact that possible more comorbidities affecting patients treated on a routine basis may have affected the compliance to therapy, the emergence of AEs, and ultimately, the outcome of the treatment itself (Table 4) as previously reported [21,22]. Therefore, if on the one hand, it is important to operate a comparison between real-life data and clinical trial outcomes, on the other, the information gathered in real-world experiences is undoubtedly valuable to help clinicians acquire familiarity with the use of new agents in several contexts of treatment.…”
Section: Discussionmentioning
confidence: 55%
“…Response rates appear instead rather similar across studies (Table 5). Likewise, discrepancies observed between patients treated in second or later line in our study and in clinical trials may be in part explained by the fact that possible more comorbidities affecting patients treated on a routine basis may have affected the compliance to therapy, the emergence of AEs, and ultimately, the outcome of the treatment itself (Table 4) as previously reported [21,22]. Therefore, if on the one hand, it is important to operate a comparison between real-life data and clinical trial outcomes, on the other, the information gathered in real-world experiences is undoubtedly valuable to help clinicians acquire familiarity with the use of new agents in several contexts of treatment.…”
Section: Discussionmentioning
confidence: 55%
“…They showed that older age does not independently influence survival and ibrutinib tolerance and confirmed that CIRS > 6 is a predictor of a poorer progression-free survival (PFS) and event-free survival (EFS). Moreover, they showed that the only baseline parameters affecting overall survival are ECOG-PS ≥ 2 and neutropenia [ 22 ]. An important consideration to make is that studies in which ECOG showed a negative impact included more unfit and, on average, older patients than those in which a higher CIRS showed an impact.…”
Section: The Evaluation Of Patients’ Fitness Statusmentioning
confidence: 99%
“…In particular, in a retrospective multicentre study [ 10 ], Gordon et al showed the impact of CIRS ≥ 7 and the severe impairment of a single organ (CIRS3+) affecting OS (2-year OS 79% versus 100%) and EFS (median 24 versus 37 months), both in frontline and relapsed CLLs [ 10 ]. Tedeschi et al, in their retrospective multicentre study [ 22 ] on 712 patients on treatment with Ibrutinib, showed that ECOG-PS ≥ 2 and neutropenia are the only baseline parameters affecting overall survival. Moreover, since it is metabolized via the CYP3A4 enzyme system, they demonstrated that the influence of concomitant medications and CYP3A-inhibitors (e.g., clarithromycin, erythromycin, diltiazem, itraconazole, ketoconazole, ritonavir, verapamil) with ibrutinib has no impact on outcome, though CYP3A4 inhibitors use severe comorbidities correlated with an increased risk of permanent dose reduction.…”
Section: Therapeutic Approaches In Older And/or Unfit Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have addressed the role of age and fitness status on BCR inhibitors management and outcome. 9 11 In two retrospective studies of ibrutinib-treated patients outside clinical trials, Cumulative Illness Rating Scale (CIRS) and ECOG-PS emerged as reliable tools in predicting treatment tolerance and survival. 9 , 11 Among other parameters considered at baseline, in the study published by Tedeschi et al , 11 only neutropenia independently influenced all the survival outcomes.…”
Section: Introductionmentioning
confidence: 99%